Correlatives and Comparative Correlatives in Angika: Syntactic Structures and Quantificational Nature - Nwogu, Aaron Ogbonnah (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
This study examines Correlatives and Comparative Correlatives in Angika, with a focus on their syntactic and quantificational properties. Building on Cinque’s (2014) unified structure of relative clauses, I explore its applicability to correlatives in Angika and argue for the presence of a right-adjoined unpronounced Degree head in Comparative Correlatives, following Bhatt and Pancheva’s (2004) analysis of comparatives. Our analysis highlights a matching effect between the relativiser and the demonstrative in Comparative Correlatives, positing that these elements function as syntactic constituents with inherent quantificational features. While Comparative Correlatives share the macrostructure of Correlatives, as argued by den Dikken (2006), I propose a distinct syntactic structure to account for their differences. Additionally, we demonstrate that prior analyses of Comparative Correlatives have been tailored to specific languages and determiner functions, necessitating a broader approach to account for Angika's unique constructions. This work contributes to a deeper understanding of the syntactic and comparative mechanisms within the Indo-Aryan family, particularly in Angika, where correlativisation remains a dominant relativization strategy.